Failed back (surgery) syndrome: time for a paradigm shift - Vleggeert-Lankamp, Carmen LAM (Br J Pain, 2013)
1. The group of patients with so-called ‘failed back surgery syndrome’ (FBSS) is very diverse. Published studies evaluating the outcome of surgical treatment vary widely in terms of surgical interventions that were performed. Results from these papers cannot be generally applied to all people who have persisting complaints after low back surgery. 2. The literature search that was performed demonstrated that the articles that scored as acceptable on assessment bias demonstrated a low to moderate patient-perceived recovery percentage. The only randomized controlled trial on this topic did not demonstrate a difference between instrumented fusion and cognitive intervention and exercise. 3. Current research does not show repeat surgery to be successful in ‘FBSS patients’, but clinical practice indicates that, in a small, carefully selected group, repeat surgery can yield rewarding results. However, parameters that make a patient prone to recover from a subsequent surgical intervention cannot be found in the literature. 4. The term ‘failed back surgery syndrome’ implies a causative role of surgery in a problem situation; failed back surgery syndrome is frequently regarded as failed back surgery. The literature does not, however, provide evidence for this. 5. It is important to inform the patient adequately to shape realistic expectations. Preoperative evaluation of parameters evaluating the psychological condition could help to better predict the outcome of surgery. 6. The term ‘failed back surgery syndrome’ has been demonstrated to be an ill-defined term, serving as a container for all kinds of back and leg problems, and wrongly implying a definite role for the surgical intervention in the aetiology. We suggest shifting the paradigm to ‘failed back syndrome’. With this term we suggest defining those patients with back and radicular leg pain without a structural deficit, or with a structural deficit that has a low a priori chance of benefiting from a surgical intervention.